PENGARUH KEPEMILIKAN ASING, UKURAN PERUSAHAAN, DAN KEBIJAKAN UTANG PADA KOS KEAGENAN - Septiawan, I Kadek Hery; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi, 2016)
This study aims to demonstrate empirically the effect of foreign ownership, company size, and debt policy to agency cost. This research was carried out on non-financial companies listed on the Indonesia Stock Exchange in the year 2012 to 2014 observations. Samples were selected by purposive sampling and acquired 74 companies that meet the criteria with 222 observations. Agency Cost proxied by asset turnover. The analysis technique used is multiple linear regression which previously have passed the test classic assumptions. Based on the analysis using multiple linear regression showed that the entire hypothesis is accepted that foreign ownership negatively affect the agency cost, the size of the company's positive effect on agency cost, as well as debt policies negatively affect the agency cost.
Keywords: foreign ownership, company size, debt policy, agency cost